Training on Designing an Attractive Website Prototype Using Figma for Students of SMK Swasta Free Methodist Medan - Subhan Hafiz Nanda Ginting; M. Rhifky Wayahdi; Fahmi Ruziq (Outline Publisher, 2024)
The training on designing website prototypes using Figma is an important step in introducing students of SMK Swasta Free Methodist Medan to the exciting and innovative world of web design. This research aims to explore the effectiveness of this training in improving their understanding of web design as well as their ability to design attractive website prototypes. The training method uses a hands-on approach, allowing students to be actively involved in the learning process. With the guidance of experienced instructors, students are invited to understand the basic concepts of web design, the use of Figma design tools, and techniques for designing effective prototypes. The results showed that the training successfully improved students' understanding of web design and their ability to use Figma to design website prototypes. In addition, students also showed improvement in their creativity in designing layouts, choosing colors, and adjusting design elements. In conclusion, the training on designing website prototypes using Figma was effective in introducing students of SMK Swasta Free Methodist Medan to the concept of attractive web design as well as improving their ability in designing creative and functional website prototypes. This kind of training has the potential to prepare students for careers in web design or web application development in the future.